Aboriginal-mainstream partnerships: Exploring the challenges and enhancers of a collaborative service arrangement for Aboriginal clients with substance use issues - Taylor, Kate; Bessarab, Dawn; Hunter, L.; Thompson, S. (2013)
Background: Partnerships between different health services are integral to addressing the complex health needs of vulnerable populations. In Australia, partnerships between Aboriginal community controlled and mainstream services can extend health care options and improve the cultural safety of services. However, although government funding supports such collaborations, many factors can cause these arrangements to be tenuous, impacting the quality of health care received. Research was undertaken to explore the challenges and enhancers of a government initiated service partnership between an Aboriginal Community Controlled alcohol and drug service and three mainstream alcohol rehabilitation and support services. Methods. Sixteen staff including senior managers (n=5), clinical team leaders (n=5) and counsellors (n=6) from the four services were purposively recruited and interviewed. Interviews were semi-structured and explored staff experience of the partnership including the client intake and referral process, shared client care, inter-service communication and ways of working. Results & discussion. Communication issues, partner unfamiliarity, 'mainstreaming' of Aboriginal funding, divergent views regarding staff competencies, client referral issues, staff turnover and different ways of working emerged as issues, emphasizing the challenges of working with a population with complex issues in a persistent climate of limited resourcing. Factors enhancing the partnership included adding a richness and diversity to treatment possibilities and opportunities to explore different, more culturally appropriate ways of working. Conclusion: While the literature strongly advises partnerships be suitably mature before commencing service delivery, the reality of funding cycles may require partnerships become operational before relationships are adequately consolidated. Allowing sufficient time and funding for both the operation and relational aspects of a partnership is critical, with support for partners to regularly meet and workshop arrangements. Documentation that makes clear and embeds working arrangements between partners is important to ameliorate many of the issues that can arise. Given the historical undercurrents, flexible approaches are required to focus on strengths that contribute to progress, even if incremental, rather than on weaknesses which can undermine efforts. This research offers important lessons to assist other services collaborating in post-colonial settings to offer treatment pathways for vulnerable populations. © 2013 Taylor et al.; licensee BioMed Central Ltd.